Educating about social issues in the 20th and 21st centuries. volume two : a critical annotated bibliography - Totten, Samuel; Pedersen, Jon E. (Research in curriculum and instruction, 2013)
Over the course of the past decade and a half, we, Samuel Totten and Jon E. Pedersen, have co-edited a series of books on teaching and learning about social issues. Our goal has been to build a series that would broadly represent the work that has been undertaken over the past 110 plus years related to the field of teaching and learning about social issues. As we created and added to the series (see for example: Addressing Social Issues in the Classroom and Beyond: The Pedagogical Efforts of Pioneers in the Field; Researching and Teaching Social Issues: The Personal Stories and Pedagogical Efforts of Professors of Education; Teaching and Studying Social Issues: Major Programs and Approaches), we came to the conclusion that the development of an annotated bibliography of the key works (books, chapters, articles, reports, and research) on a wide-range of issues/topics germane to teaching and learning about social issues was a logical addition to the series. In Educating About Social Issues in the 20th and 21st Centuries Volume 1: A Critical Annotated Bibliography (which was published in early 2012), the focus was on a host of programs, models, strategies and concerns vis-à-vis teaching and learning about social issues. This new book constitutes Volume Two in the series entitled Educating About Social Issues in the Twentieth and Twenty First Centuries and picks up where Volume One left off.Included in this book are the pioneering works of the following: Boyd Bode, Alan F. Griffin, G. Gordon Hullfish, Richard Gross, Robert Yager, and James Banks. Collectively, their work on social issues spans the period between the late 1930s through the present (with James Banks and Robert Yager continuing to publish through today). As for the subjects/topics (other than pioneers of teaching about social issues) addressed in this volume, they are: Issues-Centered Approaches to Teaching Geography, Addressing Social Issues in Sociology and Anthropology Courses, Peace Studies, The Vietnam War, and LBGT.